Fabrication of novel Fe (III), Co (II), Hg (II), and Pd (II) complexes based on water‐soluble ligand (NaH2PH): structural characterization, cyclic voltammetric, powder X‐ray diffraction, zeta potential, and biological studies. (17th October 2022) - Mohammed, Mahdi A.; Fetoh, Ahmed; Ali, Tamer Awad; Youssef, Magdy M.; Abu El‐Reash, Gaber M.
Abstract : Sodium4‐hydroxy‐3‐([2‐picolinoylhydrazineylidene]methyl)benzenesulfonate (NaH2 PH) was synthesized as a novel water‐soluble ligand, by the condensation of picolinohydrazide with sodium 3‐formyl‐4‐hydroxybenzenesulfonate. The (NaH2 PH) ligand and its isolated Co (II), Fe (III), Hg (II), and Pd (II) complexes were analyzed by elemental analysis and characterized by spectroscopic (Fourier transform infrared spectroscopy, UV–visible, powder XRD, 1 H NMR, 13 C NMR, MS) and magnetic measurements. By comparing IR spectra of both ligand and the metal complexes, one can assume that the (NaH2 PH) ligand behaves as a bi‐negative tetradentate (ONNO) in [Co (NaPH)(H2 O)2 ].3H2 O, and a mono‐negative tridentate (ONO) in [Fe (NaPH)Cl2 (H2 O)] complex, whereas in [Hg2 (NaPH)Cl2 (H2 O)] complex, (NaH2 PH) coordinates as a bi‐negative pentadentate (ONNNO) ligand via deprotonated OH group of phenolic ring (C=N)Py and (C=N*) coordinated to one of Hg (II) ion and the oxygen atom of enolic group and (C=N)az group with the another Hg (II) ion. Moreover, (NaH2 PH) acts as bi‐negative tridentate (ONO) ligand in [Pd (NaPH)(H2 O)].2H2 O complex. The geometries of complexes were suggested based on the UV–visible spectra, magnetic measurements and confirmed by applying discrete Fourier transform (DFT) optimization studies. The thermal fragmentation of both [Pd (NaPH)(H2 O)].2H2 O and [Co (NaPH)(H2 O)2 ].3H2 O complexes was performed, and the kinetic and thermodynamic parameters were computed using the Coats–Redfern and Horowitz–Metzger methods. The redox behavior of divalent ions of cobalt and mercury were discussed by the cyclic voltammetry technique in the presence and absence of (NaH2 PH) ligand. Biological potencies of the ligand and its metal complexes were evaluated as antioxidants (ABTS and DPPH), anticancer, DNA, and antimicrobial ( Staphylococcus aureus and Bacillus subtilis as Gram (+) bacteria, Escherichia coli and Pseudomonas aeruginosa as Gram (−) bacteria, and Candida albicans as fungi). Abstract : The degradation effect of the (NaH2 PH) ligand and its isolated complexes on the genomic DNA, (a) Escherichia coli DNA, (b) E. Coli DNA + DMSO, (c) (NaH2 PH) ligand, (d) Co (II) complex, (e) Fe (III) complex, (f) Hg (II) complex and (g) Pd (II) complex.